Evaluation of the effect of shift work on birth weight and gestational age ofnewborns inemployed women - O Aminian; A Rashedi; KH Sadeghniiat Haghighi (طب کار)
Abstract Background:Mother's physical activity and occupationare two factors thatare supposed to have a role in producing low birth weight and premature birth. Severe physical work is an independent risk factor for premature infants. Thisstudywas designed to evaluate the effect of shiftworkandthe amountof physical activityduring pregnancy on birth weightandgestational age. Methods:In a cross-sectional study,considering inclusion criteriawe selected 540 persons from employed womenwho were referredto hospitals for delivery in Tehran during a year.After delivery, allrequired datawas gatheredby interview andpatient records.We analyzed data by SPSS (ver. 18) using chi square,t test, one-way-ANOVAand logistic regression. Results:The mean mother's age, Newborn's birth weight, and gestational age was 25.3years, 2726±457 g, and 36.9±2.4 weeks, respectively. Inthisstudy, a significant correlation between thefrequency ofnewbornswithlow birth weight and mother's shiftwork wasobserved (p= 0.001)butthis correlation was not observed forfrequency of preterm infants. Conclusion:During pregnancy, shift work has a significant role in causing low birth weight.